FACTORS INFLUENCING THE LIKELIHOOD OF ADOPTION OF INTEGRATED STRIGA MANAGEMENT FOR AFRICA TECHNOLOGIES AMONG SMALL SCALE MAIZE FARMERS IN BAUCHI AND KANO STATES, NIGERIA - Abdullahi, S.; Idrisa, Y. L; Baribusta, D.; Abdoulaye, T. (Nigerian Journal of Agriculture and Agricultural Technology, 2022)
The study examined the adoption of integrated striga management for Africa (ISMA) technology among small scale maize farmers in Bauchi and Kano States, Nigeria. A multi-stage sampling technique was used in selecting 508 respondents from the study areas. Data were collected through the administration of questionnaire and analyzed using both descriptive and inferential statistics. The results revealed that average age of the beneficiaries and the non-beneficiaries were 39 and 38 years respectively. Majority (88.7% and 86%) of the total beneficiaries and non-beneficiaries of the ISMA project in the study area were male with an average household size, farm size and farming experience of 11 people, 3 hectares and 18 years, respectively. The results of the logistic regression revealed that, level of education and major occupation were negative and significant in influencing the likelihood of adopting ISMA technology p<0.01 while distance to sources of technology was positive and significant at the same level. The major constraints to the adoption of ISMA were, inability to differentiate desmodium from other weeds and non-availability of materials relating to ISMA technology. It can be concluded that, level of education, major occupation and income were the factors influencing the likelihood of adopting ISMA technologies in the study area. Based on the constraints highlighted, the research recommended; more on farm trials to be conducted by extension agents in order to build the capacity of the farmers on the technology and materials for ISMA technology should be made available to the farmers by the government and other relevant agencies.